Market segmentation to reflect the school's “green” context and increase the impact of environmental education - Osvaldo Eric Ramírez‐Bravo; Evangelina Camargo‐Rivera; María Guadalupe Sánchez‐Corona (Conservation Science and Practice, 2024)
Abstract Collaboration between the fields of biodiversity conservation and social marketing is growing to promote environmental awareness and induce behavioral changes. In order to assess the significance of employing market segmentation, we conducted an analysis focused on identifying the “green” characteristics of the 386 high schools in the city of Puebla, Central Mexico. We designed a 15‐item survey to evaluate “green” features on school websites, including aspects like institutional identity, facilities, curricula, and extracurricular activities. Utilizing the gathered data, we employed multivariate statistics to categorize the schools into four groups: Green schools, Interested schools, Contemplators, and Do not act, indicating their potential exposure to environmental themes. We conclude that organizations can adopt a similar approach to develop tailored activities with enduring impacts, simultaneously reducing costs and enhancing effectiveness.